Applications in basic marketing : clippings from the popular business press - McCarthy, E. Jerome (Edmund Jerome); Perreault, William D.; McCarthy, E. Jerome (Edmund Jerome).; McCarthy, E. Jerome (Edmund Jerome). (Homewood, IL : Irwin, 2005)
"Clippings from the popular business press."
Published: Boston, Mass: McGraw-Hill/Irvin, <2004/2005>
Editors: 1990- E. Jerome McCarthy and William D. Perreault, Jr.
Includes bibliographical references.
Companion vol. to: McCarthy, E. Jerome (Edmund Jerome). Basic marketing; and: McCarthy, E. Jerome (Edmond Jerome). Essentials of marketing.
Earlier selection Decision based on 1990
Title from title page.
Keywords: Marketing -- Periodicals; Marketing -- Management -- Periodicals; Marketing -- Management -- Periodicals; Marketing -- Périodiques; Marketing -- Coupures de presse -- Périodiques; Marketing